Elevating School Brand Identity: Strategic PR Optimization Through Social Media Dynamics - Balqis Hadrianingtyas; Mohammad Syahidul Haq (Journal of Educational Management Research, 2026)
School branding is a strategic aspect in strengthening reputation, attracting prospective students, and building public trust in the quality of educational institutions. In the digital era, the role of school public relations is increasingly crucial for systematically managing communication and school identity through social media. This study aims to examine how to optimize public relations management to build school branding through social media. Using a qualitative case study design, research was conducted in elementary schools as a representative sample of private schools that actively use social media. Data collection techniques include in-depth interviews with public relations staff, principals, teachers, and students' parents/guardians; observation of the school's social media content; and documentation of posts and public interactions. Data analysis is carried out through data reduction, thematic categorization, and interpretation to find patterns of digital branding strategies. The results show that a planned, consistent, and responsive public relations strategy for digital dynamics, including involving students and teachers as content creators, can increase visibility and engagement and build a positive image of the school. The most dominant and effective platforms in building branding are Instagram and TikTok, followed by Facebook and YouTube. Social media-based public relations management is a strategic need for school branding in the digital era.